BARRIERS AND RESOURCES FOR JOURNALISTS’ LIFE SUCCESS - Balashov, Eduard; Handzilevska, Halyna; Shturkhetskyy, Serhiy; Kostiuchenko, Oleksii; Shulyk, Roman (Journal of Education Culture and Society, 2020)
Aim. This research aims to theoretically characterize and empirically research the indicators of barriers and resources for journalists’ success in life through the prism of their professional scripts. The focus is on the axiological component of the professional script of media professionals. Methods. We used theoretical analysis of the psychological works aiming at studying journalists’ success in life, and such methodological instruments as the Lifetime Orienteering Test (Leontiev, 2000); an adapted version of James Crambo’s Purpose-in-Life Test (PIL); Leonard Maholiсk’s Personal Readiness for Change Questionnaire (1993), and Methodology Completeness of Life. Statistical correlation was analyzed with the use of Pearson’s correlation coefficient. Results. The theoretical analysis and empirical data revealed the correlation between the indicators of sense-of-life orientations and the indicators of personal readiness for change, script settings, perceptions of self, others and life. The results identify psychological barriers, and allocate directions of development of the technologies for optimization of journalists’ success in life. Conclusions. The results of the study made it possible to distinguish priority values-goals and values-instruments, important in the construction of the architectonics of the axiological component of the journalists’ professional script. The correlation between indicators of journalists’ middle level life-sense orientations and indicators of personal change readiness empirically confirmed a claim that innovative readiness of journalists intensified the process of reaching success in life. Psychological barriers of the cognitive process were stated as script attitudes. The development of technologies for the psychological support of journalists was considered as a prospect for our future studies.